CESifo World Economic Survey November 2004 - Gernot Nerb; Anna Stangl (CESifo World Economic Survey, 2004)
World Economic Climate: World Economic Climate approaching a cooling-down phase - Economic Expectations: Current economic situation remains above satisfactory, economic expectations have weakened somewhat - Inflation: Inflation outlook remains benign - Interest Rates: Fewer WES experts expect rising interest rates - Currencies: Euro still overvalued - Special Topic: Growth will not lead to more employment in the majority of countries, according to WES experts
Keywords: 330